Determinants of Profitability in Islamic Banks Listed on the Indonesia Stock Exchange - Iza Fardan Nuha; Irfan Firmansyah; Dadang Husen Sobana (Jurnal Maps (Manajemen Perbankan Syariah), 2026)
The profitability performance of Islamic banks listed on the Indonesia Stock Exchange (IDX) remains a critical issue, particularly regarding how capital strength, financing quality, and operational efficiency shape Return on Assets (ROA). This study aims to analyze the factors that influence the profitability of Islamic banks listed on the Indonesia Stock Exchange (IDX), measured by the Return on Assets (ROA) indicator. The main issue examined is the extent to which the Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), and Operational Costs to Operating Income (BOPO) affect the profitability performance of listed Islamic banks. The research employs a quantitative approach using secondary data from the annual financial reports of four Islamic commercial banks listed on the IDX for the 2015–2024 period, which are processed into panel data. Samples are selected using purposive sampling, and data are analyzed using panel data regression with a fixed effect model determined through the Chow and Hausman tests. The results indicate that CAR has a positive and significant effect on ROA, while NPF and BOPO have a negative and significant effect on ROA. Simultaneously, CAR, NPF, and BOPO significantly influence profitability, with the coefficient of determination showing a very strong explanatory power of the model.